Association between nutritional status, body composition, and fitness level of adolescents in physical education in Casablanca, Morocco - Oukheda, Mourad; Bouaouda, Khawla; Mohtadi, Karima; Lebrazi, Halima; Derouiche, Abdelfettah; Kettani, Anass; Saile, Rachid; Taki, Hassan (Frontiers in Nutrition, 2023)
Aim: This study aims to analyze and compare dietary intake, as well as to examine the associations between energy intake in terms of macronutrients, body composition, and physical fitness (PF) specifically cardiorespiratory endurance (CE) among a sample of young adolescents aged 15 to 18 years, who participate in physical education and sports sessions in public schools in Casablanca, Morocco.Materials and Methods: A total of 310 participants, including 156 girls and 154 boys, were included in the study. Each participant maintained a food diary for three days during the same study week. Additionally, body composition measurements were taken using bioelectrical impedance analysis (BIA). The PF was assessed using the validated mini-Cooper test (6min).Results: The results show that the participants had an average total energy intake of 2386.7 ± 492.7 kcal. A significant difference was observed between boys and girls, with average energy intakes of 2468.8 ± 531.1 kcal and 2304.0 ± 437.0 kcal, respectively. These dietary intakes were significantly lower than their needs and nutritional recommendations. The associations of nutritional status, sex, body mass index (BMI) and physical fitness (PF) were tested and a positive correlation was observed following an adequate intake of carbohydrates (CHO) and proteins on VO2max, while a negative association was observed with regard to Body fat for both sexes. Boys exhibit significantly better PF than girls (p < 0.01). Obese participants had the lowest PF and an unbalanced nutritional status, the adolescents with a normal weight p < 0.01 displayed a high level of PF compared to individuals in other weight categories.Conclusions: The PF is significantly associated with macronutrient intake status and body composition, especially BMI and BF. The Underweight, overweight, and obese students demonstrated poorer performance in physical fitness indices compared to normal-weight. Adolescents adhering to recommended CHO and protein intake levels tend to exhibit enhanced physical fitness. Implementing strategies to encourage students to maintain a balanced diet and engage in regular physical exercise is essential.